2009
DOI: 10.1063/1.3126449
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and vacancy formation of Li3N

Abstract: Articles you may be interested inMagnetic-enhanced electron-phonon coupling and vacancy effect in "111"-type iron pnictides from firstprinciple calculations The formation and electronic structures of 3 d transition-metal atoms doped in silicon nanowires J. Appl. Phys. 104, 084307 (2008); 10.1063/1.3000445 Relation between the magnetic properties and the crystal and electronic structures of manganese spinels Li Ni 0.5 Mn 1.5 O 4 and Li Cu 0.5 Mn 1.5 O 4 − δ ( 0 δ 0.125 )The electronic structure and vacancy form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
5
19
0
Order By: Relevance
“…However, we observed a magnetic moment when Li vacancy in bulk Li 3 N was created using large supercells, e.g., 2× 2×2, consistent with the previous work [40]. However, the calculated formation energy of Li vacancy in bulk Li 3 N is large (3.30 eV).…”
supporting
confidence: 89%
“…However, we observed a magnetic moment when Li vacancy in bulk Li 3 N was created using large supercells, e.g., 2× 2×2, consistent with the previous work [40]. However, the calculated formation energy of Li vacancy in bulk Li 3 N is large (3.30 eV).…”
supporting
confidence: 89%
“…[16][17][18][19][20][21][22][23][24][25] The lattice dynamic properties of Li 3 N have been investigated using inelastic neutron scattering, 26 infrared Raman spectroscopy, 27 and ab initio calculations. 22,23,28 The phonon dispersion curves of Li 3 N have been studied by Kress 26 and Zhao.…”
Section: 15mentioning
confidence: 99%
“…Wu et al 24,25 studied the electronic structure and vacancy formation of Li 3 N and LiMN (M= Co, Ni, Cu). They found that transition metal substitution significantly influence the electronic structures and the Li vacancy formation of Li 3 N. The calculations indicate that transition metal substitution mainly takes place at Li(1) sites, which agree well with the experimental observations.…”
mentioning
confidence: 99%
“…Whereas the GGA calculated value is 3.65Å, which is comparable with the previous GGA data. 44 Using the optimized lattice constants, the calculated ∆H f is -3.10 (-1.69) eV with LSDA (GGA) whereas the experimental and the previous GGA values are -1.73 eV 45 and -1.59 eV, 44 respectively. We repeated the same calculations using the QE code 46 with LSDA and got similar results to SIESTA.…”
Section: Resultsmentioning
confidence: 95%